The Service Experiences of Public Libraries during the COVID-19 Emergency in Wuhan: Three Case Studies. Issue 3 (3rd July 2021) - Kou, Yin; Chen, Ping; Pan, Jie-Xing
ABSTRACT: As the first libraries encountering COVID-19, public libraries in Wuhan developed innovative practices to deal with the emergency, which can provide great reference points for other libraries dealing with the crisis. Three of the major libraries in Wuhan, namely Hubei provincial library, Wuhan library, and Jianghan district library, were selected as cases to study how the first closed public libraries in China responded to the COVID-19 pandemic. Through an analysis of library portal news, WeChat public account tweets, social media information, and voice call discussions with librarians etc., the responses of the three libraries during the closure and reopening period can be summarised as follows: establishing an emergency management system to ensure internal team stability; disseminating authoritative information and knowledge to curb social anxiety and rumours; developing online cultural activities to dissipate the boredom of isolation at home; setting up book corners in special spaces to support government's innovative practices and to ease patients' panic; and, encouraging staff to improve resilience in the community.